The Effect of Laboratory Parameters on the Hospital Stay and Mortality in Pediatric Patients Who Underwent Lobectomy and Pneumonectomy - Ahmet Ulusan; Hilal Zehra Kumbasar Danaci; Bekir Elma; Maruf Sanli; Ahmet Feridun Isik (Medicina)
Background and Objectives: This study aims to evaluate the prognostic significance of various laboratory parameters in predicting the length of hospital stay and mortality among pediatric patients undergoing lobectomy and pneumonectomy for infectious or noninfectious diseases. Materials and Methods: This study was conducted by retrospective data analysis of 59 pediatric patients who underwent lobectomy and pneumonectomy due to variable diseases at the department of chest surgery. Pediatric patients diagnosed with variable diseases and who underwent lobectomy or pneumonectomy, patients who were hospitalized during the study period and underwent surgical intervention, and patients who had at least one laboratory parameter recorded before surgery were included in the study. Laboratory parameters included white blood cell (WBC) count, red cell distribution width (RDW), platelet (PLT) count, neutrophil count, mean platelet volume (MPV), monocyte count and lymphocyte count. Laboratory results were obtained from the patients’ most recent blood samples before surgery. In addition, derived ratios such as platelet-to-lymphocyte ratio (PLR), MPV-to-PLT ratio (MPR), MPV-to-monocyte ratio (MMR), MPV-to-lymphocyte ratio (MPVLR), monocyte-to-lymphocyte ratio (MLR) and neutrophil-to-lymphocyte ratio (NLR), and Pan-Immune-Inflammation Value (PIV) were calculated and their potential prognostic values were evaluated. Results: The mean age of the patients was 6.3 years (0–15 years). The gender distribution of the patients in the study group was determined as 36 male patients (61%) and 23 female patients (39%). Lobectomy was the most commonly performed surgical procedure, accounting for 83% of cases, while pneumonectomy was applied in 17% of cases. The postoperative complication rate was observed as 34%. The mean hospital stay of the patients was calculated as 12.61 days (2–84 days), while the mortality rate was recorded as 8.5%. The relationship between the neutrophil count and the length of hospital stay is quite strong, and the r value was calculated as 0.550 (p < 0.01). PIV showed a strong correlation with length of hospital stay, with an r value of 0.650 (p < 0.01). A significant relationship was also found between PLR and length of hospital stay (r = 0.500, p < 0.01). The parameters with the highest positive effect on the hospital stay are neutrophil count (B = 0.400, p < 0.01) and PIV (B = 0.500, p < 0.01). The mean hospital stay was 10.00 days (2–30) in patients without complications and 15.00 days (5–40) in patients with complications, and this difference was also significant (p < 0.01). Finally, the mortality rate was 2.5% in patients without complications, while it was determined as 20% in those with complications (p < 0.01). Conclusions: This study determines the effects of laboratory parameters (particularly PIV, neutrophil, PLR, and NLR) on the duration of hospital stay, development of complications, and mortality and emphasizes the importance of monitoring these parameters in the treatment of infectious or noninfectious diseases.